Pemahaman Hadis Isbāl Dalam Perspektif Sosiologis - Rozian Karnedi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Understanding of Isbāl Hadiths in a Sociological PerspectiveThis study aims to further analyze the differences among Muslims in understanding the isbāl hadith focused on two questions. First, whether the isbāl prohibition contained in various pure hadiths is religious normativity or sociological reasons for particular interests. Second, how is the best way to understand the isbāl hadith prohibition. The study of this issue uses a sociological approach and thematic correlative methods. The study results found that the hadiths that prohibit isbāl are tasyri'iyyah hadith (legal /normative), but the law is not universal but conditional. It happens because the emergence of the hadiths prohibiting isbāl is inseparable from the sociological factor at that time, which was a form of rejection of the Prophet Muhammad PBUH against the jahiliyyah culture. The correlative study of the hadith found that 'illat prohibiting isbāl is khuyyala' (arrogance). The proper understanding of this hadith is a contextual understanding using the rules of ushul fiqh yadūrul ḥukmi ma'a al-'illah wujūdan wa'adaman (the application of the law is closely related to the presence or absence of 'illat). The prohibition isbāl aimed specially for people who do it because of their arrogance, not to people who do it without their arrogance